Cellular crosstalk during liver regeneration: unity in diversity - Wenzhi Shu; Mengfan Yang; Jiayin Yang; Shengda Lin; Xuyong Wei; Xiao Xu (Cell Communication and Signaling, 2022)
Abstract The liver is unique in its ability to regenerate from a wide range of injuries and diseases. Liver regeneration centers around hepatocyte proliferation and requires the coordinated actions of nonparenchymal cells, including biliary epithelial cells, liver sinusoidal endothelial cells, hepatic stellate cells and kupffer cells. Interactions among various hepatocyte and nonparenchymal cells populations constitute a sophisticated regulatory network that restores liver mass and function. In addition, there are two different ways of liver regeneration, self-replication of liver epithelial cells and transdifferentiation between liver epithelial cells. The interactions among cell populations and regenerative microenvironment in the two modes are distinct. Herein, we first review recent advances in the interactions between hepatocytes and surrounding cells and among nonparenchymal cells in the context of liver epithelial cell self-replication. Next, we discuss the crosstalk of several cell types in the context of liver epithelial transdifferentiation, which is also crucial for liver regeneration. Video abstract